SERAPAN SI DAN P SERTA PERTUMBUHAN PADI GOGO (Oryza sativa L.) YANG DIAPLIKASIKAN ABU SEKAM PADI DAN PADA MEDIUM ULTISOL - Oby Clinton Sitinjak; Nelvia Nelvia (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2019)
ABSTRACTThe main problems of rice cultivation in Ultisol medium are acid reactions, Al saturation and height P fixation, as well as low availability macro, micro nutrients especially Mo and Si. Rice plants need silicate in large quantities even though it is not an essential nutrient, therefore husk ash can be used as a source of Si. Pavailability increased by applying P fertilizer which was classified as slow realease so that fixation can be supported. The research aims to study the interaction of rice husk and rock phosphate is able to improve Si and P uptake and the growth of upland rice growth on Ultisol medium. The research was conducted at the Green House of the Faculty of Agriculture, University of Riau, Pekanbaru from January to March 2019. The research in form factorial experiment 4×3 was arranged in a completely randomized design, 3 replications. The first factor wasrice husk consist of 4 levels (0, 1,5, 3, and 4,5 ton ha-1). The second factor wasrock phosphate consist of 3 levels (0, 25, 40 kg P2O5 ha-1. The results showed the application of rice husk dose of 3 ton.ha-1 and rock phosphate dose of 25 kg P2O5 ha-1 increased Si and P uptake, P uptake efficiency, the root volume, dry weight, root canopy ratio, and plant growth rate.